Promoting the health, safety and welfare of adults with learning disabilities in acute care settings: a structured literature review. Issue 11 (28th February 2013) - Bradbury‐Jones, Caroline; Rattray, Janice; Jones, Martyn; MacGillivray, Stephen
<x xml:space="preserve">Abstract</x> Aims and objectives To present the findings of a structured literature review that aimed to identify the influences on the health, safety and welfare of adults with learning disabilities in acute hospitals. Background There is increasing evidence regarding the inadequacy of care for people with learning disabilities in acute care settings. However, few studies have specifically addressed their health, safety and welfare in such contexts. Design Four key electronic databases (Medline; PsycINFO; British Nursing Index and archive; Cumulative Index to Nursing and Allied Health Literature) were searched for relevant literature published between 2000 and 2011. Methods Publications assessed as meeting the inclusion criteria were retrieved in full. Data were extracted regarding methods used; primary aims of the study being reported; and key findings. Results Of the 3505 papers identified in the initial search, eight met the inclusion criteria. Analysis revealed six areas of influence on the health, safety and welfare of adults with learning disabilities in acute hospitals: care provision (meeting health and personal needs); communication; staff attitudes; staff knowledge; supporters; and carers (valuing their role); physical environment. Conclusions We represent these six areas diagrammatically, as concentric rings. These influence on health, safety and welfare form an inner (direct) layer and an outer (indirect) layer consisting of liaison services and education/training. This new conceptualisation of influences as being multi‐layered assists in the identification of similarly multi‐layered improvement strategies. Relevance to clinical practice Adults with learning disabilities can exert their own influence on health, safety and welfare and should be supported to make decisions about their own care. More broadly they should be involved with policy development, nurse education and research. This can be achieved through inclusive approaches, for example, inviting people with learning disabilities to input into nursing curricula or to engage in research as coinvestigators.